Modeling and Optimizing Wastewater Stabilization Ponds for Domestic Wastewater Treatment - Hafiz Qasim Ali; Osman Üçüncü (Civil Engineering Journal, 2023)
In Wastewater Stabilization Ponds (WSPs), baffle walls (BWs) have the dual benefit of reducing area requirements and increasing contaminant removal efficiency up to a certain threshold. However, this advantage is mitigated by the increased demand for construction materials, highlighting the need for optimization. Effectively optimizing WSPs to suit diverse climatic regions can substantially alleviate nationwide wastewater treatment challenges. This study focuses on optimizing WSPs across seven distinct climatic regions in Turkey. In the initial phase, a comprehensive analysis was conducted using design spreadsheets for the WSPs to determine the best configuration based on traditional methodology (TM). The results demonstrated a significant decrease in WSPs area and hydraulic retention time (RT), validating the effectiveness of BWs provision. However, this approach requires additional time and effort. Subsequently, mathematical modeling (MM) was used to further reduce the time required for the optimization process. Using the interior-point algorithm in MATLAB and the generalized reduced gradient (GRG) algorithm in MS Excel Solver, both algorithms within MM effectively decreased the WSPs area and RTby approximately 10%, while decreasing the required concrete volume by approximately 5% compared with TM. As other algorithms may yield better optimization, they can be investigated by developing specialized software for WSPs. Doi: 10.28991/CEJ-2023-09-11-014 Full Text: PDF